Managing flood in the context of education, research and partnership in Malaysia - Maidin, Siti Sarah; Yahya, Norzariyah; Othman, Marini (University of Babylon, 2019)
Several structural and non-structural measures and approaches have been implemented by the Malaysian government in order to overcome and alleviate the flood disaster. To date, Education, Partnership and Research have been identified as crucial components in forming an effective Flood Management system in Malaysia. This argument has been supported by many public and private institutions worldwide. As such, the standards and plans can be developed and implemented at district, state and federal levels. The spirits of Hyogo and Sendai were used as the guiding principles. Semistructured interviews with several responding agencies were conducted for data collection. The findings indicated that less emphasis was given to the roles of components such as Education, Partnership and Research in Flood Management. The aim of this paper is to propose an integrated system for storing, disseminating and analyzing information pertaining to Education, Partnership and Research.